2016
DOI: 10.5007/2177-5230.2016v31n62p247
|View full text |Cite
|
Sign up to set email alerts
|

Eutrofização dos recursos hídricos como ferramenta para a compreensão das doenças de vinculação hídrica

Abstract: http://dx.doi.org/10.5007/2177-5230.2016v31n62p247O saneamento ambiental inadequado afeta diretamente a qualidade da água e da vida humana. O presente estudo avaliou o estado trófico das águas e as incidências de doenças de vinculação hídrica em bacias hidrográficas com diferentes graus de urbanização na região Norte da Ilha de Santa Catarina, Florianópolis. Foram utilizados o Índice Trófico (Index Trophic- TRIX) e as informações sobre a incidência de doenças de vinculação hídrica disponibilizadas pela Secreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This is a qualitative content analysis of the documentary type proposed by Bardin (2011), which is based on the organization of data by categories. The study was based on the research of Silva and Fonseca (2016), organized into three categories involving: urban occupation, the eutrophication problem, water quality aspects, and the need for quality and quantity sewage treatment over a fi ve-year period. It was observed that urbanization, lack of environmental sanitation, high concentrations of phosphorus and nitrogen favor the eutrophication of waters.…”
Section: Introductionmentioning
confidence: 99%
“…This is a qualitative content analysis of the documentary type proposed by Bardin (2011), which is based on the organization of data by categories. The study was based on the research of Silva and Fonseca (2016), organized into three categories involving: urban occupation, the eutrophication problem, water quality aspects, and the need for quality and quantity sewage treatment over a fi ve-year period. It was observed that urbanization, lack of environmental sanitation, high concentrations of phosphorus and nitrogen favor the eutrophication of waters.…”
Section: Introductionmentioning
confidence: 99%